Risk assessment of chemical carcinogens and thresholds - Neumann, Hans-Günter (Critical reviews in toxicology, 2009)
The controversial arguments about the existence of "thresholds" for carcinogens are discussed and some conclusions are drawn: (1) The meaning of "threshold" has changed considerably during the last decades. Initially, the discussion focused on the genotoxic properties of chemicals. In dose-response studies the endpoint was tumor incidence. Later, DNA adducts represented the biologically active target dose and whether saturation of metabolic activation could lead to non-linear relationships was tested as a hypothesis. (2) In a next step, the implications of the initiation-promotion model were studied. Carcinogens with tumor-initiating properties showed linear dose-response relationships at low doses without a definable threshold, whereas those with tumor-promoting properties showed non-linear characteristics compatible with the existence of a threshold. However, the results are difficult to transfer to the human situation, and many critical endpoints are subject to other risk factors so that a meaningful value cannot be given. (3) Eventually, it turned out that most carcinogens exhibit genotoxic as well as non-genotoxic properties, and toxicity may be equally important as genotoxicity. (4) In view of the discussion for more than 60 years about the existence of thresholds for carcinogens, it is suggested that the threshold approach not be used to establish acceptable risk limits. (5) Instead of calculating an acceptable risk from cancer risk data, the recommended method is to assess the incremental contribution of exposure to the background of avoidable and unavoidable exposures by using biomonitoring data from human individuals. Such data could help in risk management, in order to reach acceptable limits of exposures on the basis of the "as low as reasonably achievable" or "ALARA" principle.